O ÍNDICE DE CONFIANÇA DO EMPRESÁRIO VAREJISTA DE IJUÍ EM 2008 - Becker, Joice T.; Zamberlan, Luciano; Sparemberger, Ariosto; Büttenbender, Pedro L.; Wagner, Adriano; Köhler, Romualdo; Graef, Nelinho D. (Salão do Conhecimento, 2013)
Resumo